Engineered EGCG‐Containing Biomimetic Nanoassemblies as Effective Delivery Platform for Enhanced Cancer Therapy. Issue 15 (25th March 2022) - Wu, Pengkai; Zhang, Haitian; Yin, Yin; Sun, Meiling; Mao, Shuai; Chen, Huihui; Deng, Yexuan; Chen, Shuai; Li, Shuo; Sun, Beicheng
Abstract: Nano‐based immunotherapy of therapeutic biomolecules is attractive but tremendously hampered by the poor delivery efficiency. This study reports a novel delivery system of fluorinated‐coordinative‐epigallocatechin gallate (EGCG), referring as FEGCG/Zn, through the integration of fluorination and zinc ions (Zn 2+ ) into EGCG. The robust therapeutics of FEGCG/Zn are measured in terms of the regulating effect on programmed cell death ligand 1 (PD‐L1), the effective delivery of diverse biomolecules, and the hitchhiking ability using living cells. Taking small interfering RNA of PD‐L1 (siPD‐L1) and erythrocytes as an example, the fabricated biomimetic system achieves excellent siPD‐L1 delivery and further improves siPD‐L1 accumulation in tumors. Finally, the combination of FEGCG/Zn and siPD‐L1 promotes antitumor immunotherapy through alleviation of T cells exhaustion by regulating PD‐L1 expression in tumor cells. The results demonstrate that FEGCG/Zn substantially regulates PD‐L1 expression and improves immune‐biomolecule delivery by forming biomimetic nanoassemblies, offering a versatile platform for cancer immunotherapy. Abstract : The fluorinated‐coordinative polymer of FEGCG/Zn as an effective delivery platform is developed for immunotherapy with functions of PD‐L1 regulating, biomolecules delivery, and living‐cell hitchhiking. Based on these features, the constructed biomimetic nanoassemblies composed of FEGCG/Zn, siPD‐L1, and erythrocytes can increase their accumulation in tumors and alleviate T cells exhaustion, resulting in enhanced cancer immunotherapy.